2004
DOI: 10.1158/1078-0432.ccr-03-0502
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-Induced Endothelial Cell Death and Tumor Vessel Thrombosis Potentiate Cytotoxic Therapy against Pancreatic Cancer

Abstract: Purpose: Despite current chemotherapies, pancreatic cancer remains an uncontrollable, rapidly progressive disease. Here, we tested an approach combining a recently described antiangiogenic drug, rapamycin, with standard gemcitabine cytotoxic therapy on human pancreatic tumor growth.Experimental Design: Tumor growth was assessed in rapamycin and gemcitabine-treated nude mice orthotopically injected with metastatic L3.6pl human pancreatic cancer cells. H&E staining was performed on tumors, along with Ki67 staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
72
0
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 35 publications
4
72
0
3
Order By: Relevance
“…The rapid and focal nature of tumor cell death may reflect acute changes in established blood flow rather than attenuation of vessel proliferation. Rapamycin can promote thrombotic occlusion of tumor vessels (46,47). We observed histologic evidence of vessel occlusion, including clogged and dilated vessels and dying cells with features of ischemic necrosis, in tumors and peritumoral regions that were similar to those described for other types of tumors treated with rapamycin (data not shown).…”
Section: Discussionsupporting
confidence: 79%
“…The rapid and focal nature of tumor cell death may reflect acute changes in established blood flow rather than attenuation of vessel proliferation. Rapamycin can promote thrombotic occlusion of tumor vessels (46,47). We observed histologic evidence of vessel occlusion, including clogged and dilated vessels and dying cells with features of ischemic necrosis, in tumors and peritumoral regions that were similar to those described for other types of tumors treated with rapamycin (data not shown).…”
Section: Discussionsupporting
confidence: 79%
“…A recent study in SCC cell lines demonstrates that inhibition of mTOR induces activation of Akt and results in antitumor effects in this tumour type (Amornphimoltham et al, 2005). In this model, as well as in other disease types such as pancreas cancer (Bruns et al, 2004), the antitumor effects of mTOR inhibitors appear to be in part related to their antiangiogenic effects. In our previous work, we have determined the susceptibility of a set of SCC cell lines both in vitro and in vivo to EGFR inhibitors (Amador et al, 2004;Jimeno et al, 2006).…”
mentioning
confidence: 69%
“…It is known that mTOR inhibitors work, at least in part, by decreasing angiogenesis (Bruns et al, 2004;Stephan et al, 2004). Western blots.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other investigators have demonstrated synergistic growth-inhibitory effects by combined treatment of gemcitabine and rapamycin in another orthotopic model of L3.6pl pancreatic cancer cells. 43 They have revealed that rapamycin induced apoptosis of endothelial cells and tumor vessel thrombosis in this model and suggested that combining rapamycin with other cytotoxic drugs could be a feasible therapy of pancreatic cancer. From these data, we speculate that an antiangiogenic effect of CCI-779 might be involved in the mechanism of its synergistic antitumor activity in this study.…”
Section: Discussionmentioning
confidence: 90%